Analysis of the PAX8 gene in congenital hypothyroidism caused: by different forms of thyroid dysgenesis in a father and daughter - (:unkn) unknown (FREUND PUBLISHING HOUSE LTD, 2004)
Thyroid dysgenesis occurs sporadically with only rare familial presentation. We report a father and daughter with congenital hypothyroidism caused by different forms of thyroid dysgenesis. The father had a severely hypoplastic thyroid gland in a normal location, whereas the daughter had an ectopic thyroid gland in a sublingual position. Her brother had a hypoplastic thyroid but was euthyroid. The involvement of the candidate gene, PAX8, as the cause of thyroid dysgenesis in this family was partially excluded by linkage analysis, and the possibility of a de novo mutation excluded by sequencing.
Keywords: thyroid dysgenesis; PAX8 gene; congenital hypothyroidism; ectopic thyroid; hypoplastic thyroid; TRANSCRIPTION FACTOR-I; THYROTROPIN RECEPTOR GENE; OF-FUNCTION MUTATION; CLEFT-PALATE; RESPIRATORY-FAILURE; FAMILIAL OCCURRENCE; 2 SIBLINGS; HYPOPLASIA; GLAND; MOTHER